Using Probability for Pathological Complete Response (pCR) as a Decision Support Marker for Neoadjuvant Chemotherapy in HER2 Negative Breast Cancer Patients – a Survey Among Physicians - Gass, Paul; Untch, Michael; Müller, Volkmar; Möbus, Volker; Thomssen, Christoph; Häberle, Lothar; Erber, Ramona; Hein, Alexander; Jud, Sebastian Michael; Lux, Michael P.; Hack, Carolin C.; Hartmann, Arndt; Kolberg, Hans-Christian; Ettl, Johannes; Lüftner, Diana; Jackisch, Christian; Beckmann, Matthias W.; Janni, Wolfgang; Schneeweiss, Andreas; Fasching, Peter A.; Nabieva, Naiba (Geburtshilfe und Frauenheilkunde, 2018)
Background In women with early breast cancer, a pathological complete response (pCR) after neoadjuvant chemotherapy is reported to be associated with an improvement of the survival. The aim of this survey among physicians was to investigate whether the probability of achieving pCR in patients with a hormone receptor-positive, HER2-negative disease encourages physicians to recommend neoadjuvant chemotherapy.Methods The study was conducted via an online survey that was sent to 493 physicians, who were either known as members of national guideline committees, heads of breast cancer centers, being high recruiters in clinical trials or leading a private practice. Participants were asked about a specific case that should resemble patients for whom it is unclear, whether they should be treated with chemotherapy.Results 113 (24.5%) physicians participated at the survey, out of which 96.5% had a work experience of more than 10 years and 94.7% were board certified in their specialty. A total of 84.1% would consider pCR for a decision concerning neoadjuvant chemotherapy. With regard to the pCR probability, 2.7 and 10.6% of the participants demanded at least a pCR rate of 5 and 10%, respectively, while 25.7% were satisfied with 20% probability, and another 25.7% with a pCR rate of 30%.Conclusions The vast majority of the long-term experienced physicians would embrace the implementation of a further method such as the prediction of pCR probability in clinical routine to support decision making regarding the necessity of neoadjuvant chemotherapy. The cut-off of around 30% pCR probability seems to be a realizable rate to distinguish patient groups.
Keywords: breast cancer; pathological complete response (pCR); neoadjuvant; chemotherapy